Fluorescence light microscopy of pulmonary surfactant at the air-water interface of an air bubble of adjustable size. - Knebel, D (2002)
The structural dynamics of pulmonary surfactant was studied by epifluorescence light microscopy at the air-water interface of a bubble as a model close to nature for an alveolus. Small unilamellar vesicles of dipalmitoylphosphatidylcholine, dipalmitoylphosphatidylglycerol, a small amount of a fluorescent dipalmitoylphosphatidylcholine-analog, and surfactant-associated protein C were injected into the buffer solution. They aggregated to large clusters in the presence of Ca(2+) and adsorbed from these units to the interface. This gave rise to an interfacial film that eventually became fully condensed with dark, polygonal domains in a fluorescent matrix. When now the bubble size was increased or decreased, respectively, the film expanded or contracted. Upon expansion of the bubble, the dark areas became larger to the debit of the bright matrix and reversed upon contraction. We were able to observe single domains during the whole process. The film remained condensed, even when the interface was increased to twice its original size. From comparison with scanning force microscopy directly at the air-water interface, the fluorescent areas proved to be lipid bilayers associated with the (dark) monolayer. In the lung, such multilayer phase acts as a reservoir that guarantees a full molecular coverage of the alveolar interface during the breathing cycle and provides mechanical stability to the film.